Analisis Anteseden Variabel Intrapreneurship Behavior Pada Dosen Perguruan Tinggi Swasta Di Yogyakarta - Arief Darmawan; Maisaroh Maisaroh (UNIVED Press, 2023)
Increasing competition for higher education institutions in Indonesia requires internal changes for each organization in preparing a competitive strategy in order to survive in the current environment. Growth and survivability have been the most common goals. Intrapreneurship can be a solution to face competition in the higher education industry. Intrapreneurship is very important and appropriate to be developed among higher education in Indonesia. This research attempts to examine the role of the variable spirituality leadership as an antecedent of the intrapreneurship behavior of lecturers at private universities in Yogyakarta. The population of this study were all lecturers from private universities in Yogyakarta. Samples were taken from the population using simple random sampling techniques, and data collection was carried out by distributing questionnaires directly and online to respondents. The data analysis process uses Structured Equation Modeling (SEM) based on Partial Least Square (PLS), to test the model as well as to test the hypotheses offered. Overall, among the four hypotheses proposed, there are two hypotheses that are accepted, and two hypotheses are rejected. The research findings show that spiritual leadership has a positive and significant effect on intrapreneurship and organizational support. On the other hand, organizational support has no direct effect on intrapreneurship, and organizational support is also not a variable mediating the relationship between spiritual leadership and intrapreneurship.